P-020 Patterns of aneurysm recurrence following microsurgical clip obliteration. (4th July 2012) - Spiotta, A; Schuette, A; Moskowitz, S; Hui, F
Abstract : Introduction: Microsurgical clip obliteration remains a time-honored and viable option for the treatment of select aneurysms with very low rates of recurrence. We studied clipped aneurysms that were found to have recurrences to better understand the patterns and configuration of these rare entities. Methods: A retrospective review was performed of two prospectively maintained databases of aneurysm treatments from two institutions (Cleveland Clinic and Emory University) that spanned 14 years to identify patients with recurrent previously clipped intracranial aneurysms. Results: Twenty-six aneurysm recurrences that were previously treated with clipping were identified. Three types of recurrence were identified; Type I proximal to the clip tines, Type II distal, and Type III lateral. The most common type of recurrence was that arising distal to the clip tines (46.1%) and the least frequency encountered recurrence was that arising proximal to the tines (19.2%) Laterally located recurrences were found in 34.6% of cases. Conclusion: We have described three different patterns of aneurysm recurrence with respect to the clip application and have identified three types; those occurring proximal, distal or lateral to the clip tines. However, it is not possible to discern which of these represent true aneurysm recurrences as opposed to incomplete initial treatments and subsequent enlargement of a residual. Further study of aneurysm recurrences would have to be performed in a prospective manner with closer scrutiny of microsurgically clipped aneurysms. Competing interests: A Spiotta: Integra Neurosciences, Hemedex. A Schuette: None. S Moskowitz: None. F Hui: None.